METHOD OF DETERMINING OPTIMAL MULTIPROGRAM CONTROL PARAMETERS ON ISOLATED INTERSECTIONS - A. S. Kashtalinsky; P. N. Maluygin; V. V. Petrov (Вестник СибАДИ, 2017)
This paper demonstrates the relevance of accounting of traffic flows variability over time allows reducing intersection traffic delays in urban areas. The method of determining the optimal parameters of multiprogram control, allows considering the daily and hourly traffic flows variability was developed. Application of the optimized parameters of multiprogram control allows reducing intersection traffic delays up to 10-40% during a day compared to single-program control.